The agency between images: the relationships among ghosts, corpses, monks, and deities at a Buddhist monastery in Thailand - McDaniel, Justin (Material religion, 2011)
The ghost, Mae Nak, is well-known in Thai Buddhism as a protector of soldiers, pregnant mothers, and young lovers. Her shrine at Wat Mahabut (a monastery in Bangkok) is an important center of worship, astrology, and ritual protection. However, her statue is not alone. It is part of the pantheon of famous monks, "Hindu" deities, and Buddhas at Wat Mahabut. They draw power from each other. The relationship between these images, and what they can teach us about the study of Buddhist material and visual culture, is the subject of this study. The sacredness of a Thai Buddhist image often lies not in its origin and style, but in the relationships it creates and allows. Observing the complexity of Buddhist images and the ritual life surrounding them at this monastery helps expand and question Alfred Gell's theory of the agency of images and the "art nexus," as well as Michael Taussig's theory of "distraction."